The Efficacy of Cinnamon Extract ( Cinnamomum burmannii ) on Reducing Staging Acute Kidney Injury in Ischemia Reperfusion (IR) Model - Evi Lusiana; Nia Savitri Tamzil; Desi Oktarina (HM Publisher, 2021)
A B S T R A C TIntroduction. Acute kidney injury (AKI) is defined as sudden decline in theglomerular filtration rate, resulting in the retention of nitrogenous wastes, such asurea and creatinine in plasma. Cinnamomum burmannii is known as a anti-inflammatory renoprotective agent, although the precise mechanism is not wellunderstood. This study aimed to elucidate the effectiveness of Cinnamomumburmannii extract in decreasing creatinine level of acute kidney injury Ischemiareperfusion (IR) model. Method. We performed Ischemia reperfusion (IR) in maleWistar rat to induce acute kidney injury. The rat (n=30) were divided into six groups:IR, 1 group treated with methylprednisolone as a control (IR+M), 3 groups treatedwith different oral Cinnamomum burmannii extract doses (50mg/kg (IR+EKM1),100mg/kg (IR+EKM2), and 200 mg/kg (IR+EKM3), and a Sham operation (SO)group. AKI stage reduction based on serum creatinine levels, before and aftermodeling, before and after the cinnamon extract intervention. Creatinine levels werequntified by spectrophotometry and analyzed by SPSS. Result. Cinnamomumburmannii extract lowers creatinine levels; significant (P <0.05). 200 mg / kgbb isthe effective dose of lowering creatinine levels in the IR model. Conclusion.Cinnamomum burmannii extract reduced serum creatinine levels associated withdecreased acute renal staging in the IR model.